(untitled) (Journal of Nepal Physical Society, 2024)
This study reports the structural, electronic, and magnetic properties of undoped and halogen (F, Cl, and Br) doped ZnO monolayers (3 × 3 × 1) by replacing one Zn-atom. Using spin polarized Density Functional Theory (DFT) in VASP code and a projected augmented wave basis set, we employed GGA-PBE and PBE+U exchange correlation functionals. The band gap of pristine ZnO was measured to be 1.67 eV and 2.61 eV for PBE and PBE+U, respectively, whereas band gap decreased significantly upon addition of halogen atom. Likewise, doped ZnO shows semimetallic behavior, whereas undoped ZnO exhibits semiconducting behaviour. Further, the magnetic moments of about 1 µB for Cl and Br-doped ZnO, and 1.02 µB & 2.98 µB for F-ZnO utilizing PBE and PBE+U functionals, respectively were observed. These findings suggest that halogen-doped ZnO might carry huge potential for next-generation spintronic nanodevices.